Managing impressions: performance and identity in police leadership in the pandemic - Rowe, Michael (Policing and society, 2025)
Critical leadership scholars have long recognised leadership as performative and reveal the symbolic, presentational and ritual aspects of leadership practice as meaning-making. This perspective, however, is neglected in mainstream understanding of police leadership. Drawing on Goffman’s dramaturgical framework and a qualitative study of policing leaders in the UK, this paper explores performativity and police leadership in the context of the COVID-19 pandemic. Removed from occupational symbols of the police station and performing leadership work exclusively in the home environment, the findings show that police leaders used the uniform as part of a strategy of impression management to construct front and back stage regions in the domestic sphere. In frontstage settings, the uniform was used to represent occupational authority and reinforce a sense of shared, professional identity and purpose, despite the physical separation between leaders and their staff. Alongside this, police leaders constructed and maintained backstage spaces for preparatory and reparative work, even within the home-working setting. The findings challenge traditional conceptualisations of the backstage as physical, boundaried space of the police station and instead reveal backstage space as fluid, dynamic and imagined. As police constabularies consider the impact of remote-working practices on the police workplace, the preservation of backstage spaces for police leaders during the COVID-19 pandemic reveals the value and necessity this backstage work in police leadership.